2021
DOI: 10.1038/s42003-021-02848-x
|View full text |Cite
|
Sign up to set email alerts
|

A miniature dialysis-culture device allows high-density human-induced pluripotent stem cells expansion from growth factor accumulation

Abstract: Three-dimensional aggregate-suspension culture is a potential biomanufacturing method to produce a large number of human induced pluripotent stem cells (hiPSCs); however, the use of expensive growth factors and method-induced mechanical stress potentially result in inefficient production costs and difficulties in preserving pluripotency, respectively. Here, we developed a simple, miniaturized, dual-compartment dialysis-culture device based on a conventional membrane-culture insert with deep well plates. The de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 53 publications
3
15
0
Order By: Relevance
“…To address this problem, we include the gellan gum-based-biopolymer FP001 to reduce the mechanical stress and excess agglomeration while enabling e cient high-density culture at the same time 17,18 . Based on our previous study 7 , the application of this biopolymer has shown its potential in protecting the high-density hiPSCs aggregates from mechanical stress induced-apoptosis and necrosis, which may negatively affect cell proliferation and cell quality. In this study, we con rmed that the inclusion of this biopolymer has shown its potential to improved the HLCs production (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To address this problem, we include the gellan gum-based-biopolymer FP001 to reduce the mechanical stress and excess agglomeration while enabling e cient high-density culture at the same time 17,18 . Based on our previous study 7 , the application of this biopolymer has shown its potential in protecting the high-density hiPSCs aggregates from mechanical stress induced-apoptosis and necrosis, which may negatively affect cell proliferation and cell quality. In this study, we con rmed that the inclusion of this biopolymer has shown its potential to improved the HLCs production (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A physical condition, such as excessive mechanical stress may signi cantly affect the differentiation e ciency into the hepatic lineage. Although a gentle dynamic culture system has been known to improve the hepatic differentiation 12,13 , the mechanical stress coming from hydrodynamic mixing and aggregates collision in rotational culture may negatively interfere with the differentiation process 7 . The previous study by Vosough et al was shown that excessive shear stress can reduce the hepatic differentiation e ciency during culture in stirred tank bioreactor 14 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the usage of cytokine or growth factors still becoming a necessity, an alternative solution is developed to optimize the usage of growth factors efficiency during differentiation. For example, using a specific molecular weight cutoff dialysis membrane barrier to recycle and accumulate the high molecular weight endogenous and exogenous growth factors while continuously maintaining the exchange between the small molecular weight nutrition and toxic metabolic byproducts [83]- [86]. This approach may significantly improve the production efficiency per unit of hPSCs-derived organoids.…”
Section: High-cost Productionmentioning
confidence: 99%